2020
DOI: 10.3390/en13040978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organ-Pipe Chamber Geometry on the Frequency and Erosion Characteristics of the Self-Excited Cavitating Waterjet

Abstract: Erosion experiments were performed to uncover the impact of organ-pipe chamber geometry on the frequency and erosion characteristics of self-excited cavitating waterjets. Jets emanating from self-excited nozzles with various organ-pipe geometries were investigated. The upstream and downstream contraction ratios of the organ-pipe resonator were changed respectively from 1.5 to 6 and 2 to 12. Pressure sensors and hydrophone were used to characterize jets’ frequency characteristics. Mass loss was also obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The schematic diagram of the organ-pipe nozzle used in the experiments is shown in Figure 3. Based on previous research on the self-excited oscillating jet produced by the organ tube nozzle [37,38], preliminary experiments were carried out to determine the optimal chamber length range suitable for the experimental conditions in this study to produce strong impact pressure oscillations. Seven nozzles were tested with different oscillation chamber lengths (i.e., L c = 7.5, 9, 10.5, 12, 13.5, 15, and 16.5 mm), and other structure parameters are summarized in Table 2.…”
Section: Experimental Setup 21 Experiments Apparatus and Proceduresmentioning
confidence: 99%
“…The schematic diagram of the organ-pipe nozzle used in the experiments is shown in Figure 3. Based on previous research on the self-excited oscillating jet produced by the organ tube nozzle [37,38], preliminary experiments were carried out to determine the optimal chamber length range suitable for the experimental conditions in this study to produce strong impact pressure oscillations. Seven nozzles were tested with different oscillation chamber lengths (i.e., L c = 7.5, 9, 10.5, 12, 13.5, 15, and 16.5 mm), and other structure parameters are summarized in Table 2.…”
Section: Experimental Setup 21 Experiments Apparatus and Proceduresmentioning
confidence: 99%
“…Liu et al [17] investigated a double-hole nozzle and the aggressive ability of cavitating jets was significantly improved in contrast to the single-hole nozzle. Cai et al [18][19][20] extensively researched the cavitation characteristics of a self-resonance pulsed organ pipe nozzle. They examined the influence of nozzle geometry, including the nozzle lip and upstream and downstream contraction ratios, on these characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the grooves [20] and the roughness [21] on the inner surface of the nozzle will increase the energy disturbance of the jet and promote the generation of cavitation clouds. A study on the chamber structure of the SEON in the literature [22] showed that the pulse intensity of the cavitation jet was affected by changing the structural parameters of the SEON. The increase of pulse intensity in the self-excited oscillation cavitation jet is due to the transient accumulation and release of jet energy by the cavitation vortex ring in the self-excited oscillation chamber.…”
Section: Introductionmentioning
confidence: 99%